The yellow rose : racial stratification in a Mexican American community - Verdugo, Richard R. (Hispanic population in the United States (Charlotte, N.C.), 2019)
"The volume examines the effect racial stratification had on the economic and social lives of Mexican Americans and Anglo residents in a community that was majority Mexican American. The impact was felt economically as the community was a one-crop economy, and also in creating social disharmony between Mexican Americans and the politically and economically dominant Anglo community. This is an historical study since it is based on a survey conducted in 1969. It is one of only a few complete Mexican American community studies ever conducted."--